2012
DOI: 10.1111/j.1468-1331.2012.03702.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective case series of outcomes following spinal cord infarction

Abstract: Despite their comorbidities and limited change in AIS, these patients had significant improvement in functional abilities during impatient rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…8,18,19 Patients with an infectious aetiology also appear to have some notable differences compared with those with spinal cord infarction. 18 Regarding the pattern of complications, those with an infectious aetiology have a higher prevalence of spasticity and a lower prevalence of pneumonia. Furthermore, they have a much better improvement in their AIS grade, which explains their significant improvement in bladder, bowel and mobility functioning, as shown in Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…8,18,19 Patients with an infectious aetiology also appear to have some notable differences compared with those with spinal cord infarction. 18 Regarding the pattern of complications, those with an infectious aetiology have a higher prevalence of spasticity and a lower prevalence of pneumonia. Furthermore, they have a much better improvement in their AIS grade, which explains their significant improvement in bladder, bowel and mobility functioning, as shown in Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…3 Overall, some degree of initial recovery is observed in the majority of patients regardless of etiology, although the maximal recovery period appears to be soon after infarct. 16 Furthermore, there are no data regarding recurrence risk, making it difficult to counsel patients. Given the potential for permanent neurologic disability, however, it is not unreasonable to advise patients to limit activities that load the spinal column.…”
Section: Figurementioning
confidence: 99%
“…Some functional improvement is commonly observed over time, which might not be verified on the American Spinal Injury Association (ASIA) impairment scale. Independent gait can be achieved in cases of incomplete SCI, whereas up to 60% of patients remain wheelchair bound [6,9,18,21]. Another study reported more favorable short-term outcomes, which was present in two-thirds of patients, whereas 25% of patients did not show any clinical improvement on leaving the hospital [10].…”
Section: Clinical Presentation Etiology and Prognosismentioning
confidence: 94%
“…SCI in the setting of cardiac arrest and acute aortic rupture or dissection, and those with high cervical lesions are at greatest risk for fatality [5]. Patients with SCI have a persistently elevated mortality rate after hospital discharge [5,6,11,18,20,21]. In the largest study of 115 patients with SCI, 5-and 10-year survival rates were 55% and 42%, respectively [5].…”
Section: Clinical Presentation Etiology and Prognosismentioning
confidence: 98%
See 1 more Smart Citation